Morphological and genomic comparisons of Hawaiian and Japanese Black‐footed Albatrosses (Phoebastria nigripes) using double digest RADseq: implications for conservation. (13th June 2015) - Dierickx, Elisa G.; Shultz, Allison J.; Sato, Fumio; Hiraoka, Takashi; Edwards, Scott V.
Abstract Evaluating the genetic and demographic independence of populations of threatened species is important for determining appropriate conservation measures, but different technologies can yield different conclusions. Despite multiple studies, the taxonomic status and extent of gene flow between the main breeding populations of Black‐footed Albatross (Phoebastria nigripes), a Near‐Threatened philopatric seabird, are still controversial. Here, we employ double digest RADseq to quantify the extent of genomewide divergence and gene flow in this species. Our genomewide data set of 9760 loci containing 3455 single nucleotide polymorphisms yielded estimates of genetic diversity and gene flow that were generally robust across seven different filtering and sampling protocols and suggest a low level of genomic variation (θ per site = ~0.00002–0.00028), with estimates of effective population size (Ne = ~500–15 881) falling far below current census size. Genetic differentiation was small but detectable between Japan and Hawaii (FST ≈ 0.038–0.049), with no FST outliers. Additionally, using museum specimens, we found that effect sizes of morphological differences by sex or population rarely exceeded 4%. These patterns suggest that the Hawaiian and Japanese populations exhibit small but significant differences and should be considered separate management units, although the evolutionary and adaptive consequences of this differentiation remain to be identified.